The THE EFFECT OF DIVERSIFICATION STRATEGY ON FINANCIAL PERFORMANCE WITH GOVERNANCE AS A MODERATING VARIABLE - Estu Widarwati; Nurul Hamidah; Nunik Nurmalasari (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2023)
Financial performance is an important factor and needs to be considered by companies, because financial performance is always needed to evaluate the performance of a company and the performance of a certain period of time. One of the efforts made by the company to improve its performance is to carry out a diversification strategy. A diversification strategy requires proper management in order to optimize its performance. The existence of proper governance can assist decision-making in choosing a diversification strategy to improve the company's financial performance. The goal to be achieved in this research is the effect of diversification strategy on financial performance with governance as a moderating variable. The object of research applied in this study is to analyze the effect of the diversification strategy using the Hierschman Herfindah Index (HHI) proxy on financial performance using the Return on Equity (ROE) proxy with governance as a moderating variable proxied by Managerial Ownership and the Board of Commissioners. This study uses a quantitative approach because the data is in the form of statistical analysis numbers, further research is descriptive verification because it tests the hypothesis. The population in this study are financial companies listed on the IDX. The sample in this study was 15 companies in non-financial companies on the IDX for the 2016-2021 period. This research is a panel because it combines cross section and time series data, and is tested using the E-views9 software application. Based on the results of the study, it is known that the results of the diversification strategy t test have a significant negative effect on financial performance with firm size as a control variable. The results of the MRA H2a test show that managerial ownership strengthens the effect of diversification strategies on finances. The results of the H2b MRA test show that the Board of Commissioners weakens the effect of the diversification strategy on financial performance. The implication in this study is that the diversification strategy carried out by non-financial companies listed on the IDX for the 2016-2021 period has not provided optimal results on company performance. However, the existence of a supervisory mechanism in the form of managerial ownership has proven to be able to encourage managers to make decisions that can reduce the total risk of a diversified company. And it is necessary to increase the supervision of the board of commissioners in diversified companies in order to improve their financial performance.